Electrolyte transport in the renal collecting duct and its regulation by the renin–angiotensin–aldosterone system. (8th January 2019) - Yamazaki, Osamu; Ishizawa, Kenichi; Hirohama, Daigoro; Fujita, Toshiro; Shibata, Shigeru
Abstract : Distal nephron of the kidney plays key roles in fluid volume and electrolyte homeostasis by tightly regulating reabsorption and excretion of Na +, K +, and Cl − . Studies to date demonstrate the detailed electrolyte transport mechanisms in principal cells of the cortical collecting duct, and their regulation by renin–angiotensin–aldosterone system (RAAS). In recent years, however, accumulating data indicate that intercalated cells, another cell type that is present in the cortical collecting duct, also play active roles in the regulation of blood pressure. Notably, pendrin in β-intercalated cells not only controls acid/base homeostasis, but is also one of the key components controlling salt and K + transport in distal nephron. We have recently shown that pendrin is regulated by the co-ordinated action of angiotensin II (AngII) and aldosterone, and at the downstream of AngII, mammalian target of rapamycin (mTOR) signaling regulates pendrin through inhibiting the kinase unc51-like-kinase 1 and promoting dephosphorylation of mineralocorticoid receptor (MR). In this review, we summarize recent advances in the current knowledge on the salt transport mechanisms in the cortical collecting duct, and their regulation by the RAAS.